TRANSFORMATIVE ISLAMIC EDUCATION FROM THE PERSPECTIVE OF KH. HASYIM ASHARI IN THE BOOK OF ADAB AL-ALIM WA AL-MUTA'ALLIM - Aulia, Mizar; Salminawati, Salminawati; Dahlan, Zaini (Universitas Indraprasta PGRI, 2025)
This research is directed to trace the background conditions both external and internal KH. Hasyim Asy'ari, how the idea of transformative Islamic education KH. Hasyim Asy'ari in the book Adab Al-Alim Wa Al-Muta'allim and how the contribution of transformative Islamic education thinking KH. Hasyim Asy'ari about the idea of transformative Islamic education in the context of contemporary Islamic religious education. The type of research used is Library Research and uses a Historical Approach. The primary data source is the Book of Adab Al-Alim Wa Al-Muta'allim by KH Hasyim Asy'ari. The secondary data sources are books by KH. Hasyim Asy'ari and the works of other researchers who discuss the thoughts of KH. Hasyim Asy'ari. In analyzing the data, content analysis is used. The findings of this study are first, KH. Hasyim Asy'ari was a great Indonesian scholar and founder of the largest Islamic organization, Nahdlatul Ulama (NU), known by the nickname Hadratus Sheikh which means Great Teacher. Second, in his concept, education must integrate spiritual, intellectual, moral, and social dimensions holistically. KH. Hasyim Asy'ari's transformative ideas are also reflected in his views on learning evaluation which is comprehensive, including assessment of understanding of knowledge, practice in daily life, and its transformative impact on the personality of students. Third, KH. Hasyim Asy'ari had a significant impact on the development of the modern pesantren education system. Pesantren Tebuireng which he founded became a model for the development of an Islamic education system that integrates traditional values with modernity.